Seropositivity of Leptospira in rodents, shrews, and domestic animals in Unguja, Tanzania (Journal of Ideas in Health, 2023)
Background: Leptospirosis is one of the most commonly neglected zoonoses in developing nations including Tanzania. This study aims to find out the seroprevalence of leptospirosis in rodents, shrews, and domestic animals in different regions in Unguja Island, Tanzania. Methods: A cross-sectional study was carried out from January to April 2022. The blood samples were collected from rodents and shrews (n=248), cattle (n=247), goats (n=130), sheep (n=32), and dogs (n=80). The blood samples were allowed to clot in a slanted position and serum samples were harvested. A microscopic agglutination test (MAT) was performed on the sera to check for leptospiral antibodies using five Leptospira serovars as antigens (Sokoine, Lora, Pomona, Grippotyphosa and Hebdomadis).Results: The overall seropositivity of leptospiral antibodies was 9.68% in rodents and shrews, 14.57% in cattle, 10.01% in goats, 31.25% in sheep, and 26.25% in dogs. The seropositivity of Leptospira varied significantly with animal species (OR=1.9, 95 % CI:1.1-3.3, p=0.03). The most frequently detected serovar was Sokoine (27.89%), followed by Pomona (19.47%), Lora (18.26%), Grippotyphosa (17.98%), and Hebdomadis (8.16%), respectively.Conclusion: Our study suggests that further research should be conducted to find out factors of high seropositivity of leptospiral in Unguja. Vaccination of domestic animals with vaccines against local Leptospira strains should be encouraged, and rodent control and public awareness should be emphasized.